The Relation Between Intraocular Pressure Level and Polycystic Ovarian Disease (Eurasian Medical Research Periodical, 2022)
Polycystic ovarian syndrome (PCOS) is the most common endocrinopathy among women of reproductive age. PCOS affects around one in every five females in the reproductive age group, with a frequency of around 17 percent. Recently, female sex hormones have been demonstrated to possess systemic as well as ocular effects. Androgen, estrogen, progesterone receptors are present in the lens, cornea, the ciliary body, iris, the retina, lacrimal glands, meibomian glands, and the conjunctiva